Direct Influence of Socio-Economic Towards Education Quality: Growth of Standardization - Perales, Roland D.; Familara, Shaira Dane M.; Pena, Ramilyn T. Dela; Mabag, Anna Monica V.; Aban, Emy P.; Martinez, Junecia L.; Mohammad, Nhelbourne K. (Buletin Edukasi Indonesia, 2023)
Socio-economic is derived from the term socio, which means "social" or "socialization," while economics is defined as how societies allocate limited resources to satisfy unlimited wants and needs. In essence, socio-economics bridges the gap between economics and sociology, acknowledging that economic outcomes are often intertwined with social factors and that both play a crucial role in shaping the dynamics of societies and the livelihood of their members. Socio-economic impacts on education underscore the need for proactive efforts to ensure that all students have equal access to education quality and opportunities regardless of their background. Addressing these disparities is essential for fostering a more inclusive and equitable educational system and promoting social and economic progress. Some parents choose their children not to go to school because of their income status; they decide to get employed instead of continuing their studies to sustain the necessities of their family. The significance of this article is to identify the main problems of society, which are poverty and unemployment due to lack of access to education quality. It has been found that socioeconomic factors have a significant impact and influence on our education. Hence, as people attain a higher level of education, the more they can get quality employment status in the future.